2013
DOI: 10.1002/cpp.1871
|View full text |Cite
|
Sign up to set email alerts
|

Attribution of Somatic Symptoms in Hypochondriasis

Abstract: The misinterpretation of bodily symptoms as an indicator of a serious illness is a key feature of the criteria and the cognitive-behavioural models of hypochondriasis. Previous research suggests that individuals suffering from health anxiety endorse attributions of physical disease, whereas persons with elevated general anxiety have the tendency to attribute psychological causes to their symptoms. However, whether a somatic attribution style is specific to patients with hypochondriasis, as opposed to those wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 37 publications
3
18
1
3
Order By: Relevance
“…However, there are important differences between the construct of HA and AS in regard to the appraisal/attribution of bodily anxiety symptoms. In HA, patients tend more to attribute such symptoms to a moderate or severe physical disease process and tend to be characterized by long periods of anxiety due to the delayed consequences, whereas for people with high AS, particularly PD patients, somatic symptoms are more commonly attributed to cognitive/psychological factors (e.g., I will get crazy ) and also related to immediate threats . Nevertheless, in the current study, HA and AS (measured by the ASI) were found to be the most strongly correlated measures within individuals, and by contrast the lowest cross‐twin correlation.…”
Section: Discussioncontrasting
confidence: 71%
“…However, there are important differences between the construct of HA and AS in regard to the appraisal/attribution of bodily anxiety symptoms. In HA, patients tend more to attribute such symptoms to a moderate or severe physical disease process and tend to be characterized by long periods of anxiety due to the delayed consequences, whereas for people with high AS, particularly PD patients, somatic symptoms are more commonly attributed to cognitive/psychological factors (e.g., I will get crazy ) and also related to immediate threats . Nevertheless, in the current study, HA and AS (measured by the ASI) were found to be the most strongly correlated measures within individuals, and by contrast the lowest cross‐twin correlation.…”
Section: Discussioncontrasting
confidence: 71%
“…This, in turn, gives rise to behavioural responses (E), which persist because they reduce anxiety and/or fear in the short term, but also contribute to maintaining high levels of health anxiety over time. In accordance with the model (Figure 1), there is experimental evidence to support the claim that individuals with high levels of health anxiety are more prone than others to view healthand illness-related stimuli as threats to their own personal health 17,159 (A-B), and to direct their attention to such stimuli 16, 160-162 (C). Individuals with high levels of health anxiety also tend to have a biased perception of health-related cues, such as their own heart rhythm 163,164 ; a finding which ties in with a large empirical literature on the influence of expectancy over perception 165,166 , including interoceptive awareness 167 .…”
Section: A Cognitive-behavioural Modelsupporting
confidence: 70%
“…Severe health anxiety has a broad set of cognitive, behavioural, and emotional characteristics. For example, individuals with this condition are prone to react to disease-related stimuli 16 , and are more likely than others to interpret bodily symptoms as indicative of disease 17 . On average, individuals with severe health anxiety also utilise more health care than others 18 .…”
Section: Categorical Versus Dimensional Perspectivesmentioning
confidence: 99%
“…prolonged headache) to participants, who then have one minute per symptom to spontaneously attribute possible causes. Neng and Weck (2015) reported one notable study in which the Attribution Task is used to compare symptom attributions among patients with hypochondriasis, patients with anxiety disorders and healthy controls. In this study, two independent blind raters classified the given attributions into different categories: normalizing, somatic (diseases) and psychological.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, two independent blind raters classified the given attributions into different categories: normalizing, somatic (diseases) and psychological. By using this instrument, Neng and Weck (2015) showed that hypochondriasis is associated with a disorder-specific attribution style that connects somatic symptoms primarily with moderate (e.g. migraine) and severe (e.g.…”
Section: Introductionmentioning
confidence: 99%